Model Pengembangan Karir Pegawai Berperspektif Gender dalam Organisasi Publik - Laurensius P Sayrani; Siska Sasmita (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2008)
Human resource (HR) is strategic factor for organization including public organization in reaching its purpose. HR as strategic factor thereby must developed with various mechanism and method which can push optimalisation of potency by all officer. Career expansion models in one of mechanism which can be designed by management of organization to push every officer to application at the same time develops its ladder and responsibility. In practical level, human resource potency in this case men and woman in accessing development opportunity of career they well. Construction gender in public organization both for yielded internally (organizational management) and also external reflact situation of social embosoming which certain gender type, especially woman hindered in developing her potency. Condition will affect at organization performance that's not optimal, because HR potency cannot be powered carefully. Therefore, career expansion models based on gender perspective can adopt problems, requirement of men and especially for woman, will become necessary instrument for organization in reaching its purpose effectively.